Bankruptcy Potential on Stock Prices with Dividend Policy as a Moderating Variable: A Study of Food and Beverage Companies - Anwar; Nurman; Deddy Ibrahim Rauf (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Stock prices as the main element in the capital market, are influenced by various factors, one of which is the company's financial condition. Companies with poor financial conditions tend to experience pressure on their stock prices, which can lead to potential bankruptcy. This research intends to examine the impact of bankruptcy risk on stock prices, using dividend policy as a moderating factor, in food and beverage firms listed on the Indonesia Stock Exchange during the years 2019-2023. The study sample included 24 companies chosen via purposive sampling. The method for data analysis utilized Moderated Regression Analysis (MRA) through the Econometric Views (E-Views) version 12 software. The secondary data utilized was derived from financial reports accessed through the official IDX website. The findings of the research show that the potential for bankruptcy significantly influences stock prices. Furthermore, dividend policy has been demonstrated to enhance the connection between bankruptcy risk and stock prices, suggesting that it can act as a stabilizing element in preserving stock price stability during challenging financial situations. This study provides practical implications for company management in determining the right dividend policy as a bankruptcy risk mitigation strategy.